Satisfaction and experiences with healthcare among urban-dwelling young adult lesbian women in New York City: An exploratory analysis. Issue 3 (3rd July 2021) - Griffin, Marybec; Jaiswal, Jessica; Halkitis, Perry N.
Abstract: Young adult lesbian women (YALW) face unique barriers to healthcare access as providers do not perceive a need for sexual and reproductive healthcare services for this population. A brief survey was conducted with 100 YALW to explore healthcare experiences including: usual source of healthcare, coordination of healthcare, and satisfaction with the healthcare services provided by their primary care provider (PCP). Data collection took place between June and October 2016 at selected LGBT-friendly events and venues (i.e. Pride events, bars, community-based organizations). Nearly one fourth of the sample reported their usual source of care as a walk-in based facility (i.e. emergency room, urgent care facility, government sponsored clinic). Satisfaction with healthcare provided was more likely among participants who were comfortable discussing their sexual activity with their providers. These finding suggest that the healthcare system is not engaging YALW in routine care provided in facilities that offer continuity of care. While walk-in models may meet the immediate healthcare needs of this population, the period of young adulthood is a critical time to establish healthcare behaviors. Furthermore, understanding the patterns of healthcare access among YALW warrants further attention as the structure and nature of the healthcare system in the United States is changing.